ANALISIS KINERJA ANGGOTA MGMP BIOLOGI SMA KOTA PEKANBARU DALAM PENGEMBANGAN PROFESI - Depimei Nita Mahedra; Evi Suryawati; Yustina Yustina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was conducted to find out how the performance of members of Pekanbaru High School Biology MGMP in professional development was conducted from January 2019 to April 2019. This research was a descriptive study and used a survey research design with a cross-sectional type design, ie data collection was done once at a time . Data collection techniques in this study were carried out by distributing questionnaires, observations, interviews and documentation. At the time of distribution of the questionnaire there were two stages, in the first stage the questionnaire was distributed to members of the Pekanbaru City Biology MGMP for the purposes of questionnaire validation and reliability tests to 10 validators who were members of the Pekanbaru City Biology MGMP. At the stage of validation and reliability testing there are several items that are invalid so that revisions are made to items that are invalid. Furthermore, in the second stage, the revised questionnaire was distributed to 30 respondents who were members of the Pekanbaru City Biology MGMP which were used as research data to be analyzed and interpreted. The overall results of the analysis of the performance of Pekanbaru High School Biology MGMP members in professional development obtained a mean score of 3.44 and were in good criteria, with the results obtained as follows: motivation, creativity, selft efficacy, attitude showed very good criteria. Self development shows good criteria. Scientific publications show sufficient criteria, and for innovative works show good criteria. Thus it is known that members of Pekanbaru City High School Biology MGMP have a good performance in professional development.Key Words: Teacher Professional Development, Motivation, Creativity, Selft Efficacy, Attitude, Self Development, Scientific Publication, Innovative Work